Potassium Fractionation and Stock in Clay Soils: Influence of Geochemical and Mineralogical Properties in Yogyakarta Region, Indonesia - Eko Hanudin; Padana Aperta Barus; Makruf Nurudin; Sri Nuryani Hidayah Utami (Universitas Sebelas Maret, 2025)
Research on potassium (K) dynamics in upland clay soils, particularly those derived from tertiary-aged rocks, remains limited in Yogyakarta. This study aimed to investigate the relationships among geochemical indices, K fractions, and K stock in upland clay soils, considering the influence of their physical, chemical, and mineralogical properties. Thirty soil samples were collected from five geological formations at two depths (0 to 20 and 20 to 40 cm), with three replicates selected from each formation through purposive sampling. Soil characterization was performed using routine methods, energy-dispersive X-ray fluorescence (EDXRF), and X-ray diffraction (XRD) analyses. Geochemical indices such as the chemical index of alteration (CIA), Vogt residual index (VR), alumina to potassium oxide ratio (AKN), silica to sesquioxide (Si/Seq), and Ruxton ratio (R) were calculated, and K stock was determined. The results showed that feldspar contributes to K stock in upland clay soils. Spearman’s correlation analysis revealed that only the AKN index significantly correlated with K-pseudo-total and K-non-exchangeable (p < 0.01). The highest K-pseudo-total concentration was found in P4-Sentolo (1,326 to 1,715 mg kg-¹) and the highest concentrations of K-non-exchangeable were observed in P5-Kebobutak (1.37 to 1.78 cmolc kg-¹). Significant correlations between K-exchangeable and K-water-soluble with total organic carbon and K-non-exchangeable were also identified (p < 0.01). The highest K-exchangeable concentration was recorded in P2-Nglanggran (0.17 to 0.33 cmolc kg-¹), while the lowest was found in P1-Wonosari (0.04 to 0.09 cmolc kg-1). All clay soils exhibited K-exchangeable concentrations below the critical deficiency level. Understanding these relationships is crucial for effective soil management and sustainable agricultural production. Targeted fertilization strategies can be developed based on the dominant K fraction in each soil.